Integrating Marketing Strategy: Destination Image and Digital Marketing's Impact on Tourist Interest in Banyuwangi - Ahmadi, Raden Khaeru; Purnomo, Eko Priyo; Hadiyati, Ernani (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 18 Nomor 2 Tahun 2024, 2024)
This study aims to analyze the effect of Destination Image and Digital Marketing on tourist interest in Banyuwangi as a tourism destination. This research was conducted using qualitative data analysis (QDAS) methods and data was collected through a survey of 150 respondents who visited tourist destinations in Banyuwangi. The results revealed that Destination Image and Digital Marketing play an important role in generating tourists’ interest to visit Banyuwangi. However, several aspects need to be improved in Banyuwangi Tourism's digital marketing strategy, such as improving the quality of digital content, collaboration between stakeholders, and increasing the target market. Strategic recommendations include further investment in creative and interactive social media campaigns, continuous updates to the destination's official website, and the development of mobile applications that add users' value. By implementing these recommendations, the government and tourism industry players can ensure that Banyuwangi continues to develop as an attractive and competitive tourist destination. Keyword : Integrated Marketing Strategy; Destination Image; Digital Marketing; Tourist Interest